Lumbar Microdiscectomy. Issue 1 (27th January 2016) - Truumees, Eeric; Geck, Matthew; Stokes, John K.; Singh, Devender
Abstract : In most patients, the radiculopathy associated with lumbar disc herniation resolves nonoperatively. For patients in whom nonsurgical management has failed, microdiscectomy can be considered. Today, an operating microscope is preferred because of the collinear light and magnification offered. Alternatively, loupes and a headlight may be employed. The major steps of the procedure are (1) making a 2-cm vertical incision and then developing the corridor to the lamina subperiosteally or by using serial dilation techniques; (2) confirming the level of surgery radiographically prior to incision and once the lamina has been reached and then detaching the lateral attachments of the flavum; (3) making a small laminotomy, resecting any superior facet osteophytes, then mobilizing the compressed traversing nerve root, and, in some cases, making a small annulotomy; and (4) removing loose disc fragments and performing wound closure. Most outcomes reports after microdiscectomy have been favorable for radicular symptoms. Associated back pain typically decreased as well. Common complications include recurrent disc herniation or disc herniation at another level, wound infections, and durotomy with spinal headache.